Women, Peace, and Conflict; Increasing The Capability And Number of Indonesian Women Peacekeepers in the United Nations Interim Force in Lebanon (Unifil) - Masyrofah Masyrofah; Amany Lubis (Jurnal Cita Hukum, 2022)
This study aims to analyze the role of the government in increasing the participation of Indonesian women in the UN UNIFIL peacekeeping mission in Lebanon, the approaches and strategies used by women peacekeepers while on duty at UNIFIL Lebanon. Based on Presidential Regulation (Perpres) No. 18/2014 concerning the protection and empowerment of women and children in social conflicts, in contrast to the fact that women's involvement in carrying out UNIFIL's peacekeeping mission is still weak, even though women have great potential in soft power. Women have a different approach in seeking peace between the two parties involved in the conflict or only to keep the peace from disappearing. This research is qualitative research with a statutory approach, peacebuilding, conflict resolution, international law, politics. Data collection techniques through interviews and literature studies. The findings of this study that UNIFIL is evidence of Indonesia's success in world peace missions, women peacekeepers in the TNI MPP Troops have a role that cannot be replaced by elements other than the Women's Corps of TNI and Women's Police of the Police, considering the conflict field that prioritizes the special skills of Wan TNI and Women’s Police. Apart from that, the unique socio-religious-cultural characteristics in the South Lebanese region have a fairly complex composition, including interfaith and intra-faith sensitivity, Sunni-Shi'a dimensions, the Druze sect. The readiness of Indonesian women peacekeepers is in good condition and continues to increase. This is since the potential of Indonesian women peacekeepers is an integral part of the TNI's uniqueness, namely the ability in territorial development is a distinctive characteristic of the TNI as a national army born in conditions of struggle, and its operational capabilities are closely related to raising support from the community in its area of operation.